Rainer Maria Rilke i jego „słowiańska dusza”. Praga jako rodzime miasto poety na drodze ku odnalezieniu samego siebie w swej „prawdziwej ojczyźnie” – Rosji - Wawrzynek, Karin (Studia Rossica Posnaniensia, 2015)
This article refers to the inner feelings of Rainer Maria Rilke, who is one of the most outstanding poets and prose writers of German modernism. It attempts to show Rilke’s Slavonic soul and investigates his poetry in order to find out how he tried to discover himself and find his true homeland in Russia by beginning his journey of self-discovery in his hometown, Prague.